From Teenage Inventor to Scientist: Scientometric Profiling of an Indian-American Scientist, Dr. Shiva Ayyadurai’s Research Output - Koley, Susanta; Goswami, Sutapa (Information Research Communications, 2026)
Background This study presents a comprehensive bibliometric analysis of the scholarly contributions of Dr. Shiva Ayyadurai, an Indian-American scientist best known for his pioneering work in the development of the electronic mail system. At the age of just 14, in 1978, Dr. Ayyadurai developed an early version of email while working at the University of Medicine and Dentistry of New Jersey. His system, named "EMAIL," digitally replicated the structure of the interoffice paper-based communication system, incorporating features such as Inbox, Outbox, Memo, and Attachments-laying the groundwork for the modern email systems used today. Aim The objective of this study is to provide a quantitative overview and construct a scientific profile of Dr. Ayyadurai’s academic output from 1980 to 2025. A total of 54 publications were analysed, including 26 journal articles, 4 conference papers, 11 books, 12 patents, and 1 technical report. Methodology Data was sourced primarily from Google Scholar and Wikipedia, with supplementary information from both online and offline repositories. The dataset was organized using MS Excel and Word, and standard bibliometric indicators were applied for analysis. Findings Key findings show that Dr. Ayyadurai’s publication trajectory spans 45 years, with a balanced mix of 18 non-collaborative and 36 collaborative works. His research is notably multidisciplinary, covering systems biology, computational modelling, biological engineering, and information technology. The Degree of Collaboration (DC) ranged from 0.34 to 1.00 annually, with an overall DC of 0.67. Additional metrics include a Productivity Coefficient of 0.78 and an Average Yearly Contribution of 1.17. His most productive period was between 2020-2024, during which he published 14 papers. Dr. Ayyadurai is listed as the first author in 22 publications, reflecting his leadership in research. His most frequent collaborator is P. Deonikar, with 25 joint publications over 13 years. The majority of his papers were published in the American Journal of Plant Sciences; and Health and Environmental Research Online (HERO). A country-wise distribution reveals that the USA accounts for 61.11% of his total publications. This study also examines whether this data set validates Bradford’s and Lotka’s Laws or not. Conclusion This bibliometric study offers valuable insights into Dr. Ayyadurai’s research legacy and serves as a resource for future scholars and information scientists.
Keywords: Bibliometric; Electronic mail; E-mail; Scientometric; Shiva Ayyadurai; Statistical analysis; Teenage inventor; V. A. Shiva Ayyadurai; VAS Ayyadurai; Vellayappa Ayyadurai Shiva.